Nutritional estatus and eating habits as a risk factor for non-communicable chronic diseases in nursing students at UTN. (La U Investiga, 2023)
Chronic non-communicable diseases (CNCD) have been increasing in recent years, their risk factors may be preventable. The objective of the research was to determine the nutritional status and eating habits as a risk factor for NCDs in nursing students at the UTN. The study was non-experimental, descriptive, cross-sectional in 37 students. Nutritional evaluation was performed using BMI, % body fat, % muscle, visceral fat level and cardiometabolic risk according to waist circumference; eating habits were identified through a survey on meal times, food preferences and was complemented with a scored instrument based on the Food Quality Survey (ECAAM), identifying good or poor food quality; pregnant women and students with physical disabilities were excluded. As main results, the students are in normal nutritional status (70.27%), however, there is more than a quarter of the sample with excess malnutrition, 67.5% have high levels of fat percentage, 89% do not they have cardiometabolic risk, there are no students with high levels of visceral fat. Regarding eating habits, 94.5% have poor quality of food, the majority of students with a better score in unhealthy eating habits versus healthy ones. In conclusion, risk factors for NCDs are malnutrition due to excess, high fat percentage, poor quality of food and non-compliance with healthy eating habits more than unhealthy ones.
Keywords: Nutritional status, eating habits, NCCD diet quality, risk factor, students